Mathematical modelling of 18F-FDG concentration in the kidneys and urinary bladder / Farida Aimi Mustapha - Mustapha, Farida Aimi (2019)
Positron emission tomography/computed tomography (PET/CT) is a medical diagnostic imaging technique that allows identification of anatomical and quantitative assessment of physiological process in many types of cancers. Quantification of PET image enables to determine a direct relationship between the time-varying activity concentration in organs or tissues and the essential parameters that describe the biological processes at the cellular level.